Usaha Ternak Sapi Potong Di Kecamatan Ampel Kabupaten Boyolali - Fitriyani, Ratna Etik; , Dra. Hj. Umrotun, M.Si; , H. Yuli Priyana, M.Si (2016)
This research was conducted in the District Ampel, Boyolali district with the title: Beef Cattle for Business in the Ampel District". The purpose of this study are: 1) To know differences to care of beef cattle are carried out by the breeder. 2) To know the effect of treatment on the way to the development of beef cattle. 3) To know the contribution of income to the income total of the family. This study used survey method. Sources of data derived from primary data and secondary data. Analysis of the data used in this research is the analysis table, which includes frequency tabulation. And the analysis focuses on the spatial geography. The results showed that the differences of the care affects the growth of beef cattle in the area of research. The indicator is the availability of water resources in the study area. In the village of Sari temple daily weight growth of 2 to 3 kg / day and for village development Sampetan daily weights of 1.5 to 3.5 kg / day. The amount of revenue contribution to total family income of at most <50% for Candi Sari of the village from 19 respondents and the village Sampetan from 15 respondents. This shows that in the study area has a considerable influence on the income total of the family. Keywords: business, beef cattle